Impact of Energy Storage Unit on Power System Economic Dispatch: A Multi-parametric Programming Method and its Implication on Energy Storage Sizing - Fang, Baomin; Wu, Danman; Li, Yanhe; Huang, Shaowei; Mei, Shengwei (Chinese Control Conference, 2020)
The energy storage unit (ESU) is helpful for shaving the peak and filling the valley demands, as well as compensating the volatility of renewable generation. The performance mainly depends on the maximum charging/discharging power (in MW) and energy capacity (in MWh). This paper proposes a multi-parametric linear programming model to investigate and describe the impact of MW/MWh parameters of the energy storage unit on the economic operation of bulk power systems in a geometric manner. By employing duality theory, the optimal value function of the economic dispatch problem is approximated via piecewise linear functions which are convenient for visualization. The optimal value function delivers useful information on energy storage sizing subject to a given budget, which is elaborated as an application of the proposed method. The effectiveness of the model and method is validated via a modified IEEE 39-bus system.